THE CONNOTATIONS OF THE CRISIS ON THE CRYPTOASSETS MARKET - Marinela BĂRBULESCU; Alina HAGIU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
The so-called Crypto Crash marks not just a recent decline, but the most severe yet in the cryptocurrency world. Even brand-name enthusiasts of these virtual currencies have expressed concern, with some temporarily abandoning investments. Although the steep decline has eased, a tense atmosphere in the market remains. In this paper we aim to make an analysis of the market capitalization, prices, and estimated number of users and an estimation of crypto-assets adoption in the countries of the world. We also will focus on the key elements of the crypto ecosystem, including unbacked crypto, stablecoins, smart contracts and decentralised finance, structural flaws and risks, all in the context of the crisis on the cryptoassets market.